2009
DOI: 10.1080/20786204.2009.10873811
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for anaemia in pregnancy in rural KwaZulu-Natal, South Africa: Implication for health education and health promotion

Abstract: Background: Anaemia in pregnancy is a major public health problem in developing countries. It is associated with an increased risk of maternal and perinatal morbidity and mortality. A high rate of anaemia in pregnancy in the rural population of KwaZulu-Natal (30% according to national and 57% according to the World Health Organization [WHO] definition of anaemia in pregnancy) is observed. The risk factors for anaemia, particularly during pregnancy, are multiple and complex and their relative contributions are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…Our finding was in agreement with different studies conducted in different parts of Ethiopia and other country that reported higher odds of anemia among hookworm-infected women [ 31 , 17 , 32 ]. Additionally, similar studies also showed higher odds of anemia among those having co-infection of hookworm with other intestinal parasites [ 33 , 34 , 35 ]. The worm in the intestine may cause intestinal necrosis and blood loss as a result of the attachment to the intestinal mucosa and chronic infections lead to iron deficiency and anemia resulting from the excessive loss of iron [ 3 ].…”
Section: Discussionmentioning
confidence: 87%
“…Our finding was in agreement with different studies conducted in different parts of Ethiopia and other country that reported higher odds of anemia among hookworm-infected women [ 31 , 17 , 32 ]. Additionally, similar studies also showed higher odds of anemia among those having co-infection of hookworm with other intestinal parasites [ 33 , 34 , 35 ]. The worm in the intestine may cause intestinal necrosis and blood loss as a result of the attachment to the intestinal mucosa and chronic infections lead to iron deficiency and anemia resulting from the excessive loss of iron [ 3 ].…”
Section: Discussionmentioning
confidence: 87%
“…A local study based in KZN at the Empangeni Hospital indicated similar findings, where HIV infection was observed to increase the likelihood of anaemia during pregnancy and was more common among cases (56%) than among controls (37%) (OR = 2.11; 95% CI = 1.123, 3.21; p ≤ 0.005). 16 Upon initiation of ANC, screening for HIV is of great importance. This would help in the attitude, a fear of HIV testing, health system barriers, a lack of knowledge and financial barriers hinder an adolescent's access to ANC services.…”
Section: Discussionmentioning
confidence: 99%
“…The tool uses 10 criteria to assess both internal and external validity of studies based on participant selection criteria as a representation of overall population, how information is collected, and whether parameters used to determine prevalence was consistent in each study amongst participants (10). An overall risk of bias will then be determined based on the individual scores obtained for each of the 10 items and graded according to the number of high risks found: low (≤ 2), moderate (3)(4), and high (≥ 5). Where information related to the 10 items is not available, it will be captured as high risk.…”
Section: Risk Of Bias and Quality Assessmentmentioning
confidence: 99%